MECHANISM OF FORMATION OF THE SYSTEM OF MANAGEMENT OF FINANCIAL AND ECONOMIC POTENTIAL OF ENTREPRENEURIAL STRUCTURES ON THE BASIS OF AN INNOVATIVE APPROACH - GAVRISH, Olha; ROGATIUK, Vadym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The modern economic environment is characterized by a rapid pace of change and increased dynamics of economic activity, increased competition, uncertainty of financial markets and rapid intensive progress in the field of digitalization. In the conditions of this process, traditional methods of managing the financial and economic potential of entrepreneurial structures lose their effectiveness and need to be updated. This necessitates the search for new approaches to the formation of conditions for the sustainable functioning of business entities, increasing their flexibility, innovative activity and adaptability to the challenges of the modern market. Financial and economic potential is one of the key components of the competitiveness of an enterprise, since it determines the ability of an entrepreneurial structure to function effectively, invest in development, introduce innovations and ensure profitable activities in the long term. At the same time, the mechanism for managing this potential needs not only improvement, but also transformation based on an innovative approach, which involves the introduction of the latest management technologies, digital tools, data analytics and strategic development models.In the context of the current economic instability, globalization and the rapid development of innovative technologies, the role of effective management of the financial and economic potential of entrepreneurial structures is significantly increasing. However, most business entities face difficulties in timely response to external challenges, efficient use of resources, increasing the innovative ability to ensure long-term growth, which indicates structural shortcomings in management processes, in particular, the lack of a comprehensive, adaptive and scientifically grounded mechanism capable of ensuring a purposeful transformation of the financial and economic potential of enterprises in accordance with the requirements of the innovative economy.Modern conditions for the activity of business structures are determined by significant competition and rapid changes in the markets, instability of the external environment and growing needs for strategic renewal of management processes. In such conditions, the key factor in ensuring the long-term efficiency and sustainability of the development of enterprises is the financial and economic potential, which reflects the totality of resources, opportunities and management decisions that can ensure a sustainable growth in the value of the enterprise. Creating an effective system for managing this potential requires the introduction of modern tools and approaches, in particular those based on innovative principles. An innovative approach to management allows not only to optimize internal business processes, but also to adapt the management system to new challenges, contributing to the growth of competitiveness and sustainable development of enterprises.The mechanism for forming a system for managing the financial and economic potential of entrepreneurial structures on the basis of an innovative approach is a key tool for ensuring sustainable development, competitiveness and adaptability of enterprises in the modern conditions of the transforming economy. The innovative orientation of management processes allows you to combine strategic vision with operational flexibility, ensure the efficient use of resources, as well as implement modern digital and analytical tools for making informed management decisions. The proposed approach to the management of financial and economic potential is based on the principles of consistency, adaptability, innovation and strategic management. Its implementation allows not only to form an effective internal infrastructure of the entrepreneurial structure, but also to create conditions for its long-term development, including minimizing risks, increasing productivity and increasing market value.
Keywords: mechanism of formation; financial and economic potential; innovative approach; competitiveness; innovation strategies; management system